Basic statistics for the behavioral sciences - Heiman, Gary W. (Wadsworth/Cengage Learning, 2014)
Offering a conceptual-intuitive approach, this popular book presents statistics within an understandable research context, deals directly and positively with student weaknesses in mathematics, and introduces new terms and concepts in an integrated way.